Matrine promotes NT3 expression in CNS cells in experimental autoimmune encephalomyelitis. (10th May 2017) - Zhang, Ming-Liang; Zhang, Xiao-Jian; Kang, Jian; Zhang, Hui-Jun; Chen, Xiao-Long; Liu, Nan; Liu, Shu-Qing; Ma, Wen-Di; Zhang, Guang-Xian; Zhu, Lin
Highlights: Matrine (MAT) effectively ameliorate clinical signs and demyelination of ongoing EAE. MAT treatment enhances Neurotrophin 3 (NT3) expression in microglia, astrocytes and OPCs. MAT induced NT3 expression in both M1/M2 microglia, especially in Arg1+ M2 cells. We conclude that MAT therapy for EAE acts, at least in part, by stimulating glial cells to produce NT3. Abstract: Neurotrophin 3 (NT3) is a potent neurotrophic factor for promoting remyelination and recovery of neuronal function; upregulation of its expression in the central nervous system (CNS) is thus of major therapeutic importance for neurological deficits. Matrine (MAT), a quinolizidine alkaloid derived from the herb Radix Sophorae Flavescent, has been recently reported to effectively ameliorate clinical signs in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), by secreting antiinflammatory cytokines. In the present study, our goal was to investigate whether MAT could affect NT3 expression of glial cells in the CNS, the major cell populations in the CNS foci of MS/EAE. We found that MAT markedly upregulated NT3 expression in the CNS not only by microglia/macrophages and astrocytes, but also by oligodendrocyte precursor cells, indicative of both paracrine and autocrine effects on myelinating cells. While MAT treatment reduced the numbers of iNOS + M1, but increased Arg1 + M2 microglia/macrophage phenotypes, NT3 expression was upregulated in both phenotypes. These results indicate that MAT therapy for EAE acts, at least in part, by stimulating local production of NT3 by glial cells in the CNS, which protects neural cells from CNS inflammation-induced tissue damage.